Interpretasi Dialog Antar Agama Dalam Berbagai Prespektif - Ananda Ulul Albab (LPPM Institut Pesantren KH. Abdul Chalim, 2019)
Conflicts that occur between religious communities are often caused by small problems and misunderstandings of words or actions carried out between religious people. Though harmony is an important foundation in this nation. Therefore, dialogue is present to rebuild good relations between fellow believers. Not to look for differences then to harm it. But to look for differences that exist then embrace and love each other. Dialogue also functions to build relationships that are not only in one religion, but also outside the religion. So between Islam, Christianity, Catholicism, Buddhism, Hinduism and Confucianism can always communicate well. Remembering religion is indeed not to teach divisions but to lead every Ummah to uphold humanity. Although each religion is different in its teaching, but there are still the same aspects in terms of humanity, such as teaching love, compassion, sacrifice, mutual respect between others, giving selflessly, and many more good things taught by religion. The dialogue has different meanings and meanings depending on who interprets and gives his thoughts. It also depends on the background of the person who sparked an understanding of dialogue. In this article we will discuss dialogue according to the views of several religious leaders.